Without Your Therapist: Contemplative Prayer During Treatment as a Religious Exposure Intervention to Reduce Religious Struggle and Anxious God Representation. (August 2022) - Seesink, Henk-Jan; Klokkenburg, Pieter; Schaap-Jonker, Hanneke; Ostafin, Brian D.; Wiers, Reinout W.
This case study focuses on the treatment of a 44-year-old Dutch man presenting with an anxious God representation and religious struggles according to DSM-5 criteria. Having received prior treatment for a panic disorder and alcohol use disorder, the patient was given a 60-day treatment in which the Jesus Prayer intervention was used to address his religious and spiritual problems. To our knowledge, this is the first case study involving the Jesus Prayer in the treatment of a patient. The intervention had positive effects on the patient's religious and spiritual problems concerning an anxious God representation, religious struggles, stress levels and surrender to God. The intervention may also play a supporting role in decreasing symptoms of depression and anxiety and in promoting global mental health, as reliable change index analyses revealed symptom reduction between baseline levels and at post-assessment levels for all measured symptoms, with a semi-gradual decrease over the course of treatment. These improvements were continued in a 3-month follow-up assessment, suggesting promise for the Jesus Prayer as an effective treatment method for religious and spiritual problems. Recommendations regarding the importance of assessing the religious life of patients and implementing spiritual interventions are discussed, as well as the relevance of the therapist's own assumptions when treating a religious or spiritual problem.